INCREASING THE EFFECTIVENESS OF METHODOLOGICAL EDUCATION IN THE CONTEXT OF UPDATING THE CONTENT OF PRIMARY EDUCATION - Kosimova Gullola Mullajonovna (Modern American Journals, 2026)
This article discusses the issues of increasing the effectiveness of methodological education in the context of updating the content of primary education. It analyzes the methodological training of primary school teachers based on modern educational requirements, the role of new generation textbooks and innovative pedagogical technologies. It also considers the use of interactive methods in organizing the educational process, methodological approaches aimed at developing independent and creative thinking of students. The results of the article will serve to improve the quality of primary education and develop the professional competencies of teachers.
Keywords: Primary education, updating the content of education, methodological education, educational efficiency, new generation textbooks, innovative pedagogical technologies, interactive methods, professional competence.